2018
DOI: 10.5897/ijwree2018.0783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate variability on the yield of crops in Ondo State, Nigeria

Abstract: Climate change influences crop yield vis-à-vis crop production to a greater extent in countries likeNigeria where agriculture depends largely on natural circumstances. This study assesses the effect of observed climatic variables (rainfall, temperature and relative humidity) on yield of major crops which are divided into two groups, tuber crops (cassava and yam) and fruits (pepper and tomatoes) in Ondo State Nigeria. Crop yield and climatic data were obtained from Ondo State Agricultural Development Project (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…From the four (4) scenarios produced using the different climate models, it was observed that in some regions of the country, Nigeria, an increase in crop yield would be experienced as the years go by, while in the other areas, a decrease will be experienced. Studies from different parts of the globe also painted a similar pattern to what was reported above, with [23] postulating a negative impact on crop production due to climate change while [36] reported both an increase and decrease in crop yield as noted in this particular work.…”
Section: Soybeansupporting
confidence: 78%
See 2 more Smart Citations
“…From the four (4) scenarios produced using the different climate models, it was observed that in some regions of the country, Nigeria, an increase in crop yield would be experienced as the years go by, while in the other areas, a decrease will be experienced. Studies from different parts of the globe also painted a similar pattern to what was reported above, with [23] postulating a negative impact on crop production due to climate change while [36] reported both an increase and decrease in crop yield as noted in this particular work.…”
Section: Soybeansupporting
confidence: 78%
“…In using the climate data from National Oceanic and Atmospheric Administration (NOAA), the yield of Cassava showed a significant decrease in Abia, Adamawa, Bauchi, Bayelsa, Benue, Borno, Delta, Ebonyi, Edo, Kaduna, Kogi, Nassarawa, Rivers Sokoto, Taraba, and Zamfara states, agreeing with [23], where climate change harmed the yield of tuber crops, while the other Nineteen states and the FCT showed a marked and significant increase in yield. [36] Showed that the impact of changing climate patterns on crops using wheat and maize as case studies with respect to two (2) Representative Concentration Pathways (RCP4.5 and RCP8.5) projected both an increase and decrease in yield.…”
Section: Crop Yield Changes Under Noaa Climate Scenariomentioning
confidence: 73%
See 1 more Smart Citation
“…This confirms the findings by Kirttii, Phanindra and Mishra (2010) that rainfall and temperature are the two important weather factors that affect crop productions due to their direct and indirect influences which lead to unacceptable low productions. Also, it has been observed by Obafemi and Adebolu (2018) in Ondo State, Nigeria that annual rainfall amount has a strong influence on crop yield. It is important to note however that, the significance of the climate variables in influencing production in this case could be due to the period of harvesting which in turn affects the production but these were not available.…”
Section: Results and Discussing Of Findingmentioning
confidence: 99%